THE TRAINING OF HIGHLY QUALIFIED PERSONNEL IN THE DISCOURSE OF THE BOLOGNA PROCESS: HIGHWAY VERSUS ROADSIDE - Valery V. Markin; Viktor V. Voronov (National Research Mordova State University, 2016)
Introduction: in the conditions of post-reform Russia the questions of training personnel of higher qualification has been repeatedly raised in the scientific community and one of the main issues was the question about graduate school. Especially this question became more urgent after Russia's accession to the Bologna agreement in 2003. Materials and Methods: the article examines the problematic aspects of the scientific, organizational and pedagogical factors, procedures and criteria. In the conditions of post-reform Russia the questions of training personnel of higher qualification has been repeatedly raised in the scientific community and one of the main issues was the question about graduate school. Especially this question became more urgent after Russia's accession to the Bologna agreement in 2003. The article explores the meaningful aspects of the scientific, organizational and pedagogical factors, procedures and criteria for the development and efficiency of the Institute of doctoral (Ph.D. in Russia) compared with similar - in the European Union (doctorate) on the example of its functioning in Latvia. Results: discusses specific aspects of individual factors, procedures and criteria for the development of the Institute of postgraduate studies in Russia. On the example of the European experience, it becomes better understood form of innovation, and in fact, largely a destructive program (in relation to the preservation and development of schools in the reproduction of scientific-pedagogical personnel of higher qualification) have been actively conducted for 2015-the year of the reform of the Institute of postgraduate studies in Russia. Discussion and Conclusions: according to the research results the conclusions about the directions of improvement of training of highly qualified personnel in Russia, taking into account the European experience in this field. To revert to the old functionality targeted Russian postgraduate - training of the teaching and research staff of higher qualification with doctoral degree, with the prospect of official recognition of this degree at the Ph.D. level (branches of science). "Unload" the educational program of the graduate school, primarily through the disciplines which were studied in master's and specialist degrees. In preparation for the thesis and the procedure of its protection to use foreign experience and promotion of scientific promotion in the spirit of the Bologna process while maintaining the best national traditions and stimulate the reproduction of the leading Russian scientific schools to address major fundamental and applied problems of achieving the world's priorities.